Deep purpose: why pursue it, and how to implement it - Gulati, Ranjay (Henry Stewart Talks, 2022)
Deep purpose, Stakeholders, Long-term vision, Ethics, Purpose washing, Global business leadership, Purpose branding, ESG, Social challenges